Entrepreneurial characteristics and firm performance of small and medium enterprises in Malaysian food manufacturing industry - Norzalizah Bahari (2018)
Small and Medium Enterprises (SMEs) make a significant contribution to the national economy in Malaysia and there have been concerted efforts by the government over the years to assist SMEs in setting up and expanding their business. With their smaller operations, lower capital outlay and limited human resources, the business models of SMEs are significantly different from large corporations and require a different approachThis study draws upon the concept of entrepreneur characteristics, strategic orientation and attempts to examine how such approaches help improve the performance of SMEs in Malaysia. Using the Resource-Based View as the theoretical foundation, this study has combined the entrepreneur’s entrepreneurial characteristics such as internal locus of control, need for cognition and need for achievement as enabling elements for firms to develop their sustained competitive advantage. As a consequence, this study employs market and entrepreneurial orientation as mediating variable and GSPs is employed as moderator on each variable in this research in order to reflect factors that can intervene in the actions of a firm and its performance in real life. Data were collected from SME food manufacturing firms in Malaysia using a cross sectional study design and stratified random sampling method. A total of 396 usable questionnaires were collected using conducting face to face question and answer session through the set of questionnaire and online survey method and analyzed with Covariance-Based SEM (CB-SEM). 12 out of 18 hypothesized relationships were supported. This study found internal locus of control and need for cognition have direct relationship with firm performance, while need for achievement has non-significant relationship with firm performance. Furthermore, market and entrepreneurial orientation have strong influence with firm performance that revealed significant mediating effect. GSPs also moderates the relationship between entrepreneur’s entrepreneurial characteristics, market orientation, entrepreneurial orientation and firm performance. This research makes several theoretical contributions and provides further insights on the relationship between entrepreneur’s entrepreneurial characteristics and impacts on performance of food manufacturing industry. From the managerial viewpoint, this study provides a valid and applicable framework for food manufacturing industriesto have entrepreneur who able to be competitive and enable the adoption of market and entrepreneurial orientation and the role of GSPs as moderator in their organizations. Practical contribution indicates that the reflection of entrepreneur’s characteristics and will influence on the firm’s strategy and outcomes. The implications of this study to the policy makers, academics and food manufacturing practitioners is enhancing the awareness of the intangible resources already owned by the firm and the impact of market and entrepreneurial orientation towards achieving better firm performance.This study could also be a useful tool in selecting team members for management team and evaluating applicants for partnership and joint venture potential. In other words, the selection of the business strategies and the cultural development are the practices of “actions” or the entrepreneurial characteristics of the managers/owners.